The Early Bronze Age at Tel Nagila. (2nd July 2016) - Paz, Yitzhak; Uziel, Joe
Abstract : The excavations of R. Amiran and A. Eitan at the site of Tel Nagila are best known for the Middle Bronze Age remains exposed at the site. Yet Early Bronze remains were sporadically excavated in restricted locations where the excavators deepened their investigations below Middle Bronze strata. As such, a study of the albeit limited EB remains furnishes us with an opportunity to provide a more complete settlement history of the site, as well as a limited view of ceramic tradition that was common at the site. The following paper will present the stratigraphic and ceramic information available, and suggests a rather early date within Early Bronze III of the remains, as well as evidence for Early Bronze Age I occupation of the site.